A literature review on the vehicle routing problem with multiple depots. (January 2015) - Montoya-Torres, Jairo R.; López Franco, Julián; Nieto Isaza, Santiago; Felizzola Jiménez, Heriberto; Herazo-Padilla, Nilson
Highlights: A state-of-the-art on the vehicle routing problem with multiple depots (MDVRP) is presented. Papers published between 1984 and 2014 are reviewed. Lines for further research are proposed. Abstract: In this paper, we present a state-of-the-art survey on the vehicle routing problem with multiple depots (MDVRP). Our review considered papers published between 1988 and 2014, in which several variants of the model are studied: time windows, split delivery, heterogeneous fleet, periodic deliveries, and pickup and delivery. The review also classifies the approaches according to the single or multiple objectives that are optimized. Some lines for further research are presented as well.